A comparative analysis of profitability concepts used for the appraisal of investment in durable machinery - Kramer, B. I. B. P.(Boris Ivan Bernhardt Peter) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Com.) -- University of Stellenbosch, 1965.